Gold Price Prediction Using Linear Regression and Polynomial Regression Method - Azhari, Ardi; Umniati, Naeli (InComTech : Jurnal Telekomunikasi dan Komputer, 2025)
Gold is a precious metal with high value from mining prices and usage. His ability to purchase power and gold was often used as an investment tool in protecting value and wealth (protector of value and wealth). The high demand for gold from year to year is increasing yearly. So, it is essential to have some knowledge in predicting gold prices which aims to find out the opportunities for gold prices that will happen in future. The purpose of this study is to predict the price of gold to find out the price of gold in the coming year. Predictions are made using linear regression and polynomial regression methods, which are then compared to get the best model for the dataset. The dataset used 5703 data from gold prices from 2000-2022.Keywords—Gold Prices, Prediction, Linear Regression, Polynomial Regression